PENERAPAN ALGORITMA COSINE SIMILARITY UNTUK MENGIDENTIFIKASI KEBUTUHAN BELAJAR MURID DI SEKOLAH BERBASIS DATA ANALISIS - Aruni Muprida; Azrai Sirait (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: In an educational context, Cosine Similarity can be used to compare students' learning profiles, for example based on exam results, assignments, or material preferences, to determine the level of similarity between them. The results of this calculation can help teachers design more personalized learning programs, such as providing additional material for students who are struggling or special challenges for students who have already mastered the material well. The data used in this study were learning outcomes, grades, interests, and academic activities. The purpose of this study was to implement the Cosine Similarity algorithm to identify students' learning needs. The test results for four students can be seen in Andi's final score of 0.932. The highest profile: "Needs Math Help." Recommendation: Basic arithmetic practice and reinforcement of numerical logic are recommended. Budi's score of 0.992. The highest profile: "Needs Language Support." Recommendation: Reading and writing simple sentences are recommended. Siska's score of 0.996. The highest profile: "Needs Language Support." Recommendation: Reading and writing simple sentences are recommended. Feri's score of 0.985. Highest profile: "Needs Science/Social Studies Strengthening." Recommendation: Simple experiments are recommended to improve science/social studies understanding. The designed system successfully displays analysis results in a format that is easy for teachers to understand, namely through data visualization in the form of tables, graphs, or cluster diagrams. Keywords: Cosine Similarity Algorithm, Identifying Student Learning Needs, Data Analysis. Abstrak: Dalam konteks pendidikan, Cosine Similarity dapat digunakan untuk membandingkan profil belajar murid, misalnya berdasarkan hasil ujian, tugas, atau preferensi materi, guna menentukan tingkat kesamaan di antara mereka. Hasil perhitungan ini dapat membantu guru dalam merancang program pembelajaran yang lebih personal, seperti pemberian materi tambahan bagi murid yang kesulitan atau tantangan khusus bagi murid yang sudah menguasai materi dengan baik. Data yang dugunakan dalam penelitian ini ialah data hasil belajar, nilai, minat, dan aktivitas akademik. Tujuan dalam peneltian ini ialah mengimplementasikan algoritma Cosine Similarity untuk mengidentifikasi kebutuhan belajar murid. hasil pengujian terhadap 4 siswa dapat dilihat atas nama andi hasil nilai akhir 0.932. Profil tertinggi: “Butuh Bantuan Matematika” Rekomendasi: Disarankan latihan berhitung dasar dan penguatan logika angka. Atas nama Budi dengan nilai 0.992. Profil tertinggi: “Butuh Dukungan Bahasa”. Rekomendasi:  Disarankan latihan membaca dan menulis kalimat sederhana. Atas nama Siska dengan nilai 0.996. Profil tertinggi: “Butuh Dukungan Bahasa”. Rekomendasi:  Disarankan latihan membaca dan menulis kalimat sederhana. Atas nama Feri dengan nilai 0.985. Profil tertinggi: “Butuh Penguatan IPA/IPS”. Rekomendasi: Disarankan eksperimen sederhana untuk meningkatkan pemahaman IPA/IPS. Sistem yang dirancang berhasil menampilkan hasil analisis dalam bentuk yang mudah dipahami oleh guru, yaitu melalui visualisasi data berupa tabel, grafik, atau diagram cluster. Kata Kunci: Algoritma Cosine Similarity, Mengidentifikasi Kebutuhan Belajar Murid, Data Analisis.